Analysis of Fatty Acid Composition in the Seed and flower oil of Syrian Ligustrun Lucidum and olive oil (Baghdad Science Journal, 2014)
The fatty acid composition in the seed and flower of Ligustrun lucidum and olive oil was studied by Gas Chromatography. Results showed that the main components of seed oil were Palmitic (C16:0) 5,893% ,Palmitolic acid (C16:1)0,398%, Steaeic (C18:0)2,911% ,Oleic (C18:1)74,984%,Linoleic (C18:2) 12,959%,and Linolenic (C18:3) 0,997%. The proportion of unsaturated fatty acid was above 89,338%, so the seed oil of L. lucidum ait belonged to unsaturated oil which possessed promising application. The components of flower oil were Palmitic (C16:0) 65,674% ,Palmitolic acid (C16:1)6,516%, Steaeic (C18:0)2,641% ,Oleic (C18:1)14,707%,Linoleic (C18:2) 3,113%,and Linolenic (C18:3) 2,70%. The proportion of unsaturated fatty acid and saturated fatty acid was above 26,406%, 68,315%,respectively so the flower oil of ligustrun lucidum belonged to saturated oil .the main components of olive oil were Palmitic (C16:0) 13,364% ,Palmitolic acid (C16:1)0,834%, Steaeic (C18:0)3,860% ,Oleic (C18:1) 68,668%,Linoleic (C18:2) 12,586%,and Linolenic (C18:3) 0,687%. The proportion of unsaturated fatty acid was above 82,775%, so the olive oil of ligustrun lucidum ait belonged to.These values of seed oil are very similar to that found in the olive oil.